2016
DOI: 10.1007/s10668-016-9880-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beach tourists on bathing water and sand quality at Puerto Velero, Colombia

Abstract: Fragile coastal areas suffer from human activities. Environmental quality is one of the most important aspects in a tourist destination of sun and sand. The quality of bathing water and sand became indicators in the worldwide competition of beach destinations. We studied the water and sand quality along the beach of Puerto Velero, in northern Colombia. Water and sand beach quality were monitored during thirteen months. This allowed identifying the most significant sources of pollution along the beach, and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The area investigated, i.e., the Department of Atlántico, is located in the Colombian Caribbean region and has a coastline length of approximately 64.5 km (4% of the Colombian Caribbean). Different studies have assessed seawater quality at specific places of such coastal sector, using only the detection of indicator bacteria of faecal contamination (e.g., Faecal Coliform, E. coli, Enterococcus and Clostridium) [12][13][14], but none took into account beach typology or used molecular techniques for the detection of pathogens (e.g., Salmonella spp. presence/absence).…”
Section: E Coli and Salmonella Spp Distributionmentioning
confidence: 99%
“…The area investigated, i.e., the Department of Atlántico, is located in the Colombian Caribbean region and has a coastline length of approximately 64.5 km (4% of the Colombian Caribbean). Different studies have assessed seawater quality at specific places of such coastal sector, using only the detection of indicator bacteria of faecal contamination (e.g., Faecal Coliform, E. coli, Enterococcus and Clostridium) [12][13][14], but none took into account beach typology or used molecular techniques for the detection of pathogens (e.g., Salmonella spp. presence/absence).…”
Section: E Coli and Salmonella Spp Distributionmentioning
confidence: 99%
“…Therefore, uncontrolled tourism development and unsustainable tourist flows may compromise the ecosystem services that coastal environments provide leading to negative repercussions to tourism itself (Drius et al 2019). Environmental deterioration is one of the most common causes of tourists' disappointment and drives the choice of holiday destination (Torres-Bejarano et al 2018). Consequently, today many islands are dealing with the lowering of tourism fluxes because of the deterioration of the natural environment (Dodds and Graci 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated the negative impact that uncontrolled tourism can have on the environment [6][7][8]. The effects caused by mass tourism are not limited to the coastal area where they originate but also affect the surrounding areas due to hydrological dynamics and other environmental transport mechanisms [9]. On the other hand, tourism activity in protected areas can benefit local destinations through increased income from the financial contributions of visitors, employment, and direct conservation support [10].…”
Section: Introductionmentioning
confidence: 99%